Penerapan Model Pembelajaran Modified Free Inquiry untuk Mereduksi Miskonsepsi Mahasiswa pada Materi Fluida - Noly Shofiyah (Universitas Muhammadiyah Sidoarjo, 2017)
This research aimed to reduce student’s misconceptions on fluid subject at Science Education program study, Universitas Muhammadiyah Sidoarjo (Umsida) by applying a modified free inquiry learning model. The results showed that the students’ understanding of concepts increased from the average score 21.3 to 68.3. Based on the data analysis using N-gain score, it could be concluded that the implementation of the modified free inquiry model averagely affected on reducing the studen’s misconceptions